Formulações lipossomais injetáveis análise sistemática para fins regulatórios - Marcela Záquia Fraga de Castro Cassano (2015)
Nanotechnology is growing in pharmaceutical field as an alternative for drug delivery to the target site, and includes various categories of drug carriers such as colloidal lipid systems and polimeric systems. Among these, liposomes stands out by their biocompatible and biodegradable characteristics, low toxicity and high versatility. There are many marketed liposomal drug products, most of them injectables. From a regulatory perspective, some documents were published by the FDA and EMA, but not yet carried out a systematic analysis of the factors influencing efficacy, toxicity and stability of injectable liposomal drug products in order to identify regulatory relevant items, mainly with regard to its quality control and stability. The aim of this study was to perform this evaluation using cause and effect diagrams (Ishikawa) to provide knowledge for regulatoryaction and to support the development of regulations or guidelines containing specific requirements for injectable liposomal drug products, especially with regard to their quality control and stability. It was possible to identify: the need for reviewing the current concept of excipient; the paradoxes inherent to injectable liposomal drug products; the critical quality attributes to the efficacy, safety and stability of this products, and some of the tests to be considered in its characterization, quality control and stability. It was also identified some important aspects of the main analytical methods used for particle size and electric surface charge determination. Finally it was possible to analyze some specific topics related to Good Manufacturing Practices of injectable liposomal drug products. The regulatory process involves making decisions that requireknowledge. This work, together with the current legislation, it is useful for the regulation of injectable liposomal drug products.